Non-Muslims' Intention to Consume Halal Food in Indonesia - Joko Setyono; Arowadi Lubis (Shirkah: Journal of Economics and Business, 2023)
The effect of religiosity on intention to consume halal food among non-Muslims on a national scale has not been examined in previous studies. This research aims to gauge the acceptance of non-Muslims toward halal-certified food in Indonesia by investigating the effect of attitude, subjective norms, perceived behavioral control, and religiosity on the intention of non-Muslims to consume halal food. Data was collected from 250 respondents in each province using convenience sampling and analyzed using PLS-SEM. The results show that attitude, subjective norms, and religiosity significantly affect intention, while perceived behavioral control does not show significance. Theoretical implications of this research lie in its potential contribution to the academic discourse surrounding the acceptance of halal-certified food among non-Muslim people. Additionally, this study is expected to yield practical benefits by informing campaigns aimed at promoting halal-certified food among non-Muslims.